A New Scheme for Solving Multiorder Fractional Differential Equations Based on Müntz–Legendre Wavelets. (31st July 2021) - Bin Jebreen, Haifa; Tchier, Fairouz
Abstract : In this study, we apply the pseudospectral method based on Müntz–Legendre wavelets to solve the multiorder fractional differential equations with Caputo fractional derivative. Using the operational matrix for the Caputo derivative operator and applying the Chebyshev and Legendre zeros, the problem is reduced to a system of linear algebraic equations. We illustrate the reliability, efficiency, and accuracy of the method by some numerical examples. We also compare the proposed method with others and show that the proposed method gives better results.